Urban diagnostics and a systems approach to air quality management: Pathways towards sustainable economic development and a healthy nairobi, Kenya - Singh, Ajit; Bakare, Hakeem; Mazzeo, Andrea; Avis, William R.; Ng'ang'a, David; Gatari, Michael; Bartington, Suzanne E.; Thomas, G. Neil; Bryson, John R.; Andres, Lauren; Quinn, Andrew; Burrow, Michael; et al. (Frontiers in Environmental Science, 2022)
Taking holistic actions to improve urban air quality is central to reducing the health risks associated with urbanisation, yet local evidence-based and institutional frameworks to achieve this are still challenging especially in many low-and middle-income countries (LMICs). This paper develops and applies an integrated systemic approach to explore the state of air quality management in Nairobi, Kenya; as an LMIC exemplar city. The urban diagnostics approach developed assesses current particulate matter air pollution in Nairobi; quantifies anthropogenic emissions for the years 2015 and 2020 and projects scenarios of impacts of actions and inactions to 2030. This was combined with a review of grey literature on air quality policies, urban development and interviews with key stakeholders. The analysis suggests that commendable progress has been made to improve air quality in Nairobi but continuing hazardous levels of air pollution still require concerted policy efforts. Data available for numerical simulations have low spatial resolution and are generated from global emission inventories that can miss or misrepresent local emission sources. The current air quality data gap that needs to be addressed are highlighted. Strong political support is required to ensure that current air quality improvement approaches are evidence based to achieve long-term sustainability goals.